Qur’anic Work Ethics - Kamri, Nor â€˜Azzah; Ramlan, Siti Fairuz; Ibrahim, Azharsyah (Jurnal Usuluddin, 2014)
The Qur’an is the primary source in all Islamic matters, including in work ethics. This article attempts to discuss work ethics as scripted in the Qur’an. In overall, the values and ethics in the Qur’an could be classified into three major components, namely religious, quality and personal values. These three components have a significant impact on work culture in the organization. It is hoped that this article can enhance the understanding of Muslim employers/employees towards work ethics. This understanding will encourage them to implement work ethics in their daily activities.